Adaptation of hardy personality questionnaire in mexican population - Meda-Lara, Rosa Martha; Yeo-Ayala, Carmen; Juárez-Rodríguez, Pedro; Palomera-Chávez, Andrés; Moreno-Jiménez, Bernardo (Pensando Psicología, 2021)
Introduction: The concept of hardy personality as proposed by Kobasa is defined by three dimensions, namely: commitment, control and challenge. Moreno-Jiménez et al. (2014) designed and validated the Hardy Personality Questionnaire (CPR) in Spanish workers and this instrument has been adapted and validated in different Latin American countries; however, in Mexico it has not been psychometrically validated.Objective: The objective of this study was to analyze the psychometric properties of the adaptation of the CPR in Mexican adults.Methodology: A non-random sample of 357 adults who reported being healthy was used. The CPR was adapted to the way of facing daily life.Results: Three models were estimated in the confirmatory factor analysis. Among them, the one that showed better adjustment indexes was the trifactorial (control, involvement and challenge) with a second order factor (resistant personality), the internal consistency of the CPR was acceptable and the construct validity indicated positive correlations of the CPR dimensions with the positive variables and negative correlations with anxiety and social dysfunction variables.Conclusions: The results found indicate that CPR has satisfactory psychometric characteristics and can be used to measure hardy personality (challenge, control and involvement) in Mexican adults.
Keywords: Mexican Population; hardy personality; adaptation; psychometric validation